2014
DOI: 10.1038/nature13620
|View full text |Cite
|
Sign up to set email alerts
|

Non-equivalent contributions of maternal and paternal genomes to early plant embryogenesis

Abstract: Zygotic genome activation in metazoans typically occurs several hours to a day after fertilization, and thus maternal RNAs and proteins drive early animal embryo development. In plants, despite several molecular studies of post-fertilization transcriptional activation, the timing of zygotic genome activation remains a matter of debate. For example, two recent reports that used different hybrid ecotype combinations for RNA sequence profiling of early Arabidopsis embryo transcriptomes came to divergent conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 26 publications
5
70
0
Order By: Relevance
“…Additionally, monoallelic expression of LRE expression after fertilization in the developing seed is earlier than reported for other MEGs (Jahnke and Scholten, 2009;Ngo et al, 2012;Nodine and Bartel, 2012;Raissig et al, 2013). Because the patrigenic allele of LRE remains silent in various stages of seed development after 24 HAP Gehring et al, 2011;Hsieh et al, 2011;Nodine and Bartel, 2012;Raissig et al, 2013), our observations also cannot be explained by delayed paternal genome activation (Autran et al, 2011;Del Toro-De León et al, 2014;García-Aguilar and Gillmor, 2015). Based on these observations, we conclude that LRE expression is imprinted in both zygote and endosperm.…”
Section: Lre Expression Is Imprinted In the Zygote And Endosperm Immesupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, monoallelic expression of LRE expression after fertilization in the developing seed is earlier than reported for other MEGs (Jahnke and Scholten, 2009;Ngo et al, 2012;Nodine and Bartel, 2012;Raissig et al, 2013). Because the patrigenic allele of LRE remains silent in various stages of seed development after 24 HAP Gehring et al, 2011;Hsieh et al, 2011;Nodine and Bartel, 2012;Raissig et al, 2013), our observations also cannot be explained by delayed paternal genome activation (Autran et al, 2011;Del Toro-De León et al, 2014;García-Aguilar and Gillmor, 2015). Based on these observations, we conclude that LRE expression is imprinted in both zygote and endosperm.…”
Section: Lre Expression Is Imprinted In the Zygote And Endosperm Immesupporting
confidence: 54%
“…LRE expression after fertilization can arise from expression in either one or both tissues. Additionally, parent-of-origin-dependent gene expression has been reported in both endosperm (Gehring, 2013;Bai and Settles, 2015) and embryo (Jahnke and Scholten, 2009;Nodine and Bartel, 2012;Raissig et al, 2013;Del Toro-De León et al, 2014), two distinct cell types within an embryo sac. The RT-PCR and AS-PCR assays in Figure 1 could not distinguish LRE expression in maternal sporophytic tissues of ovules from expression in the developing embryo sac, nor can it rule out contamination of seeds with RNA from maternal tissues, as was reported for endosperm and early embryo transcriptomes in Arabidopsis (Schon and Nodine, 2017).…”
Section: Lre Expression In Seeds Is Primarily From the Matrigenic Allelementioning
confidence: 99%
“…Accession-specific transcriptional responses have been previously observed (Autran et al, 2011;Nodine and Bartel, 2012;Del Toro-De León et al, 2014), so it is not surprising that Col and Cvi accessions display variation in transcriptional profiles of reproductive cells and tissues. Interestingly, we identified members of gene families that were enriched in the Col pollination transcriptome that were absent from Cvi pollinations such as small secreted defensin-like proteins ( Figure 5D), low molecular weight cysteine-rich proteins ( Figure 5E), and NBS-LRR genes (TIR-NBS-LRR; Figure 5F).…”
Section: Gene Expression Changes Are Induced By Inter-accession Pollimentioning
confidence: 99%
“…Using this approach, we have analyzed pollen tube and pistil gene expression in crosses between Cape Verde Island-0 (Cvi) pistils and Columbia-0 (Col) pollen. Interestingly, analysis of gene expression in hybrid embryos revealed that the onset of paternal allele expression varied depending upon the combination of parental accessions (Autran et al, 2011;Nodine and Bartel, 2012;Del Toro-De León et al, 2014). Our application of this approach analyzes gene expression in reproductive tissues before formation of any hybrid cells (embryo and endosperm).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in transcriptomics made it feasible to study global gene expression of these two fertilization products and more than 100 transcriptomes from Arabidopsis thaliana embryos and endosperm have been generated to date Bartel, 2010, 2012;Belmonte et al, 2013;Autran et al, 2011;Slane et al, 2014;Xiang et al, 2011;Hsieh et al, 2011;Gehring et al, 2011;Pignatta et al, 2014). However, data from independent studies investigating parental contributions to early embryo and endosperm transcriptomes has been inconsistent, and the parental genomic contributions to early zygotic transcriptomes has remained controversial (Nodine and Bartel, 2012;Autran et al, 2011;Weijers et al, 2001;Meyer and Scholten, 2007;Del Toro-De Leó n et al, 2014). We hypothesized that inconsistencies between the studies mentioned above are due to varying amounts of RNA contaminants from cells surrounding the tissues of interest.…”
mentioning
confidence: 99%